Motivation of Secondary Education Students in Soundscape Activities: A Quasi-Experimental Study in a Context of Social Vulnerability - Angel-Alvarado, Rolando (2019)
Self-Determination Theory (SDT) establishes that self-determined behavior depends on the satisfaction of three innate psychological needs: autonomy, competence, and relatedness. In this study, we will establish the behavior that six teams of secondary education students display when carrying out creative activities linked to the soundscape, in the framework of the music subject in Chile’s education system. This quasi-experimental study is posed from the hermeneutic pedagogy as it considers the interaction between musicology and didactical intervention for interpreting student behavior in conformity with SDT. The qualitative data analysis entails the triangulation of a variety of tools, such as focal interviews and direct observation techniques. According to the results, most of the participants do not show self-determined behaviors during creative activities as they undergo both internal and external pressures within their teams. In conclusion, self-determination depends on the satisfaction of the three innate psychological needs.